Development and Evaluation of Customized Bike Saddle Pads Using Innovative Design for AM Approaches and Suitable Additive Manufacturing Processes - Sebastian Geyer; Jonas Schwemmer; Christian Hölzl (Applied Sciences)
Design for additive manufacturing (DfAM) has made significant advancements in recent years, with development focusing on pivotal aspects such as topology optimization (TO), generative design (GD), lattice structures, and AI-based algorithms. This paper puts forth a proposed methodology for the development of customizable bike saddle pads for manufacturing with AM. The approach entails the selection of appropriate AM processes and materials, the evaluation of material properties through compression testing, an initial saddle pressure mapping and bike fitting, the design and AM of bespoke saddle pads based on the initial measurements, and a validation pressure mapping and bike fitting. The investigation yielded clear findings regarding improvements in both pressure distribution and the change in pressure peaks, as well as an improvement in riding comfort. The findings indicate that although the overall process is innovative, improvements are required to streamline the measuring, modeling, and manufacturing workflow.